Analisis Break Even Point untuk Perencanaan Laba Penjualan UMKM Bawang Goreng Kemasan Tahun 2024 - Nugraha, Aditya Satria; Komari, Ana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Dapur Rumah Brambang Rinnings is a micro, small, and medium enterprise (MSME) engaged in the production of packaged fried shallots and faces challenges in profit planning due to fluctuations in the price of raw materials such as shallots. The purpose of this study is to analyze the use of the Break Even Point (BEP) method as a tool for sales profit planning to help determine the break-even point and realistic profit targets. This research employs a descriptive approach with a combination of quantitative and qualitative data. Data collection techniques include interviews, direct observation, and documentation of the MSME's financial reports. The data used consists of fixed costs, variable costs, selling price, monthly sales volume in 2024, and profit targets for 2025. The BEP analysis provides a clear picture of the minimum sales required to avoid losses, as well as the contribution margin necessary to plan profits effectively. The BEP analysis provides a clear picture of the minimum sales required to avoid losses, as well as the contribution margin needed to plan profits effectively. All three variants of the fried shallot products studied have exceeded the break-even point, with a margin of safety above 88%, indicating a high level of sales security. The 100-gram product proved to be the largest contributor to profits, while the 1000-gram product offered a high profit margin per unit despite being sold in smaller quantities. The profit planning strategy for 2025 was formulated realistically based on calculated sales volumes and selling prices for each product. This research not only aids MSME owners in making accurate business decisions but also contributes academically to the literature on BEP application in the ready-to-eat food MSME sector. It is expected that the findings of this study can serve as a reference for setting optimal pricing, production, and sales targets to support sustainable business growth.